CYCLIN‐DEPENDENT KINASE 8 positively regulates oil synthesis by activating WRINKLED1 transcription. Issue 2 (16th February 2023) - Zhai, Zhiyang; Blanford, Jantana K.; Cai, Yingqi; Sun, Jing; Liu, Hui; Shi, Hai; Schwender, Jorg; Shanklin, John
Summary: CYCLIN‐DEPENDENT KINASE 8 (CDK8), a component of the kinase module of the Mediator complex in Arabidopsis, is involved in many processes, including flowering, plant defense, drought, and energy stress responses. Here, we investigated cdk8 mutants and CDK8‐ overexpressing lines to evaluate whether CDK8 also plays a role in regulating lipid synthesis, an energy‐demanding anabolism. Quantitative lipid analysis demonstrated significant reductions in lipid synthesis rates and lipid accumulation in developing siliques and seedlings of cdk8, and conversely, elevated lipid contents in wild‐type seed overexpressing CDK8 . Transactivation assays show that CDK8 is necessary for maximal transactivation of the master seed oil activator WRINKLED1 (WRI1) by the seed maturation transcription factor ABSCISIC ACID INSENSITIVE3, supporting a direct regulatory role of CDK8 in oil synthesis. Thermophoretic studies show GEMINIVIRUS REP INTERACTING KINASE1, an activating kinase of KIN10 (a catalytic subunit of SUCROSE NON‐FERMENTING1‐RELATED KINASE1), physically interacts with CDK8, resulting in its phosphorylation and degradation in the presence of KIN10. This work defines a mechanism whereby, once activated, KIN10 downregulates WRI1 expression and suppresses lipid synthesis via promoting the degradation of CDK8. The KIN10‐CDK8‐dependent regulation of lipid synthesis described herein is additional to our previously reported KIN10‐dependent phosphorylation and degradation of WRI1.